The impact of information culture on the adoption of mobile cloud learning in higher education environments - A.Y Alqaralleh, Bassam; Zakarya Alksasbeh, Malek; AbuKahlil, Tamer; Almahafzah, Harbi (International Journal of Engineering and Technology, 2019)
Adoption of new innovated technologies has become an important requirement for a successful development and implementation of computer systems. Mobile cloud learning is a relatively recent paradigm shift that provides significant promise for meeting future education development and delivery requirements based on mobile cloud computing. The focal point of this study is to develop a conceptual model which highlights the effects of information cultural factors on the adoption of mobile cloud learning in higher education environments. The proposed model is developed based on four identified information cultural variables, namely information integrity, formality, control and pro-activeness. A pilot survey is conducted to test the questionnaire using a small sample of information systems experts and university lecturers. The results show acceptable reliability and validity of the instrument. Finally, conclusions, possible practical contributions of this study and some of the directions for upcoming research are discussed.Â Â Â